"Determinants of life-expectancy: analysis of Southeastern European countries" - Trpkova nestorovska, Marija; Levkov, Nikola (Institute of Knowledge Management, 2019)
Political, social or economic factors can significantly influence the life expectancy at birth. This is important since life expectancy is an indicator of both the quality of life and one country’s development. Governments should create strategies in order to improve the quality of life, nevertheless, they should first know the main factors that determine it. Consequently, the main purpose of this analysis is to identify the key determinants of life expectancy at birth by using the cointegrated panel regression model for twelve Southeastern European countries. The research includes annual data for period 2000-2015, for twelve countries. The countries included in this analysis are Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Cyprus, Greece, Macedonia, Moldova, Romania, Serbia, Slovenia and Turkey. Kosovo and Montenegro are not included in the analysis due to the insufficient data for the observed period. The total number of observations is 192. The analysis examines the possible statistically significant impact that the six explanatory variables (consumer price index, employment, food production index, gross national income per capita, health expenditure per capita and immunization) may have on the life expectancy. Before the regression model is estimated, variables are tested for stationarity and cointegration. The results from the cointegrated panel regression confirm that the consumer price index, employment and gross national income per capita are statistically significant determinants that influence the life expectancy at birth in the Southeastern European countries. Consumer price index has positive impact of the life expectancy, as the life expectancy continues to increase, the demand for food also increases and so does its prices. Employment to population ratio has negative and statistically significant impact, where decline in employment is mostly due to the emigration of the active work force. While the employment rate is declining, the life expectancy, partly due to the other factors, is constantly increasing, thus the negative dependence. Gross national income has positive and statistically significant effect on the life expectancy. The result is in accordance with the expectations because greater the gross national impact per capita means better standard of living with quality housing, education, health providers, quality food. Solid economy is precondition for improvement of life expectancy and thus quality of living. Having economic factors as key determinants of life expectancy is important input while creating government policies and measures that could contribute to better quality of living.
Keywords: Life expectancy at birth, cointegrated panel regression, GNI per capita, employment